American Desi - Gopal, Jyoti Rajan; Kelkar, Supriya, 1980- (New York : Little, Brown and Company, 2022)
An American child of East Asian descent revels in dances, clothing, games, foods and other characteristics of both cultures, while blending them into what makes this American desi unique.
Keywords: East Indian Americans -- Juvenile fiction; Identity -- Juvenile fiction; Stories in rhyme; East Indian Americans -- Fiction; Identity -- Fiction; Picture books; Stories in rhyme